2014
DOI: 10.1002/2013wr014849
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating spatial dependence in regional frequency analysis

Abstract: The efficiency of regional frequency analysis (RFA) is undermined by intersite dependence, which is usually ignored in parameter estimation. We propose a spatial index flood model where marginal generalized extreme value distributions are joined by an extreme-value copula characterized by a max-stable process for the spatial dependence. The parameters are estimated with a pairwise likelihood constructed from bivariate marginal generalized extreme value distributions. The estimators of model parameters and retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…This model can be interpreted as the superposition of an infinite number of normal‐shaped storms centered at location ξ i and having severity γ i . The model has found practical applications in the study of spatial extremes; see, for example, Coles (), Shang, Yan, and Zhang (), and Wang, Yan, and Zhang (). Although the model is anisotropic in general, an isotropic random field occurs if one lets Λ 12 =Λ 21 =0 and Λ 11 =Λ 22 .…”
Section: Some Copula Models Suitable For Spatial Modelingmentioning
confidence: 99%
“…This model can be interpreted as the superposition of an infinite number of normal‐shaped storms centered at location ξ i and having severity γ i . The model has found practical applications in the study of spatial extremes; see, for example, Coles (), Shang, Yan, and Zhang (), and Wang, Yan, and Zhang (). Although the model is anisotropic in general, an isotropic random field occurs if one lets Λ 12 =Λ 21 =0 and Λ 11 =Λ 22 .…”
Section: Some Copula Models Suitable For Spatial Modelingmentioning
confidence: 99%
“…Matalas & Langbein, 1962;Stedinger, 1983;Hosking & Wallis, 1988). To deal with the issue of inter-site correlation Wang et al (2014) incorporated spatial dependence into an index-flood model and showed significantly increased accuracy in return level estimates in Switzerland, compared to the L-moment method. In orographic regions, like Norway, RFA can be particularly challenging due to the large spatial variation of precipitation and the difficulty in defining homogenious regions (e.g.…”
Section: Generalized Extreme Value (Gev) Distributionmentioning
confidence: 99%
“…Another example in spatial extremes modeling is regional frequency analysis. Covariates can also be incorporated into the GEV scale and shape parameters (e.g., Wang, Yan, and Zhang 2014), in which case, the CSE method can be applied to one set of parameters at a time given others in an iterative estimation procedure.…”
Section: Cse Methodsmentioning
confidence: 99%